The impact of environmental protection tax on the health of middle-aged and older adults: evidence from CHARLS data in China - Wang, Hao; Zhou, Ruifan; Luo, Haohan; Liang, Shanwen; Kong, Youzhuan (Frontiers in Public Health, 2024)
With the aging population, the relationship between human health and the ecological environment has gained increasing attention. In China, it is imperative to evaluate the policy effects of the Environmental Protection Tax (EPT) on improving the ecological environment and enhancing the health of middle-aged and elderly people. This study, based on data from the China Health and Retirement Longitudinal Study (CHARLS), employs a Difference-in-Differences (DID) model to assess the health effects of the EPT policy. The findings indicate that the EPT policy significantly improves the health of middle-aged and elderly individuals and reduces the prevalence of chronic diseases. The EPT policy affects the health of middle-aged and elderly people through two main mechanisms: emission reduction and psychological effects. These are evidenced by reductions in PM10 particle concentration and sulfur dioxide emissions, improvements in public sleep quality and memory, and significant changes in environmental awareness and concern. Heterogeneity analysis reveals differences across urban and rural areas, age groups, and education levels. Following the implementation of the EPT policy, there are notable improvements in reduction of chronic diseases among rural residents, self-rated health among urban residents, and overall health among the elderly and individuals with a junior high school education or lower. The study's results confirm the importance of environmental policies in promoting public health, providing a reference for the refinement of the EPT system, and offering insights for environmental pollution control in developing countries.